EFFECTS OF PHYSICAL AND CHEMICAL MODIFICATION ON BIOLOGICAL ACTIVITIES OF CHITOSAN/ CARBOXYMETHYLCELLUSE BASED HYDROGELS - Benghanem, Saida; Chetouani, Asma; Elkolli, Meriem; Bounekhel, Mahmoud; Benachour, Djafar (Journal of the Chilean Chemical Society, 2017)
Hydrogels network based on carboxymethylcellulose (CMC) and chitosan (CS), CC1 and CC2, have been prepared respectively in the presence or without the crosslinking agents [(N-hydroxysuccinimide (NHS)/N,N’-dicyclohexylcarbodiimide (DCC)] and characterized by FT-IR. The swelling behavior in distilled water at 25°C and biological activities have been investigated. CC1 hydrogel revealed higher potential swelling than CC2. Hydrogels showed to possess an important antioxidant activity equal to 66.67% for CC1 and 57.27% for CC2, to scavenge hydroxyl radicals at 2mg/mL. And the values of their reducing power were approximately 53% and 57%. From the hemolytic potential test the obtained materials were hemo-compatible. The anti-inflammatory activity exhibited that hydrogels were able to protect albumin from denaturation.